Hubungan Kepemilikan Asuransi Kesehatan dengan Metode Persalinan di Kabupaten Sleman Analisis Data Health and Demographic Surveillance System (HDSS) Sleman Tahun 2015-2021 - Ramdhani, Suci; Ratrikaningtyas, Prima Dhewi; Wiratama, Bayu Satria (Riviera Publishing, 2025)
Cesarean section (CS) is a critical medical intervention that can save the lives of mothers and babies when performed based on proper clinical indications. However, the rising global and national CS rates raise concerns about unnecessary interventions without medical necessity. The World Health Organization (WHO) recommends an ideal CS rate of 10–15%, yet the global average has reached 18.6%. In Indonesia, the 2023 National Health Survey reported a CS rate of 25.9%, while in Yogyakarta Province it was 38.1%. In Sleman Regency, HDSS data showed an increase from 26.11% (cycle 3) to 34.63% (cycle 5), remaining above WHO’s threshold despite a slight decline afterward. This study applied a retrospective cohort design using Sleman HDSS data from 2015–2021, involving 853 mothers who met inclusion criteria. Data were analyzed with chi-square tests and multivariate logistic regression using STATA to examine the relationship between health insurance ownership and CS, controlling for sociodemographic factors. Results revealed that 68.58% of mothers delivered vaginally, while 31.42% underwent CS. Health insurance ownership was high (73.95%) but showed no significant association with delivery method (AOR = 1.13; 95% CI: 0.79–1.61). Significant factors influencing CS were maternal age >31 years (AOR = 4.96), urban residence (AOR = 1.75), and gestational age >43 weeks (AOR = 5.05), while higher parity reduced CS likelihood (AOR = 0.38). Maternal education and employment were not significant predictors.